PROSPECTS FOR THE TREATMENT OF METASTATIC GASTRIC CANCER - Adilkhodjaev A.A; Khusnuddinov N.Z; Yunusov S.Sh (Scholar Express Journals, 2023)
The surgical method is the main method of treatment for almost all types of malignant neoplasms of the stomach. For patients who cannot undergo radical resection or with metastatic disease, comprehensive treatment based on systemic antitumor therapy such as palliative surgery, radiation therapy, radiofrequency ablation (RF), intraperitoneal perfusion and arterial embolization is recommended, as they can help prolong survival and improve quality of life. Such cases should be discussed in an interdisciplinary commission for an optimal personalized treatment strategy
Keywords: gastric adenocarcinoma; anti-angiogenic chemotherapy